Alternative substrates in different containers for production of conilon coffee seedlings - Jaeggi, Mário Euclides Pechara da Costa; Saluci, Julio Cesar Gradice; Rodrigues, Rogério Rangel; Gravina, Geraldo de Amaral; Lima, Wallace Luis de (Coffee Science - ISSN 1984-3909, 2018)
Different substrates and containers influence the production of coffee seedlings, which can reduce production costs, both with alternative substrates and with containers of smaller volumes of substrates. The aim the present study was to evaluate the viability of alternative substrates in different containers for production of Conilon coffee (Coffea canephora Pierre ex Froehner) seedlings in the nursery of the Federal Institute of Espírito Santo - Campus of Alegre, ES, Brazil. The experimental design was a randomized complete block design with three replications, in split-plot with three plots and four subplots. The plots consisted of three containers (120 cm³ tube, 280 cm³ tube and 615 cm³ bag), and the subplots of four substrates (S1 - Conventional, S2 - Legume compost, S3 - Grass compost, S4 - Vermicompost). At 165 days after sowing, the evaluated variables were shoot and root dry mass, number of leaves, shoot height, leaf area, Dickson quality index, shoot/root ratio, root length, nitrogen and total crude protein. The alternative substrates (Legume compost, Grass compost and Vermicompost) were efficient for production of Conilon coffee seedlings and can replace the conventional substrate at this development stage, providing good quality seedlings. The major developments were observed in the containers with the highest volume (280 cm³ tube and 615 cm³ bag) and reflected directly on the quality of seedlings.